2011
DOI: 10.1055/s-0031-1279756
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Therapeutic Considerations for “Mycotic” Cerebral Aneurysms – 2 Case Reports and Review of the Literature

Abstract: Cerebral aneurysms of an infectious origin often have a disastrous clinical course in which morbidity and mortality can be reduced by early diagnosis, appropriate antimicrobial therapy, and aneurysm elimination by an experienced team. Apart from the initial treatment, major attention should be focused on a thorough follow-up to confirm complete cure of the primary site of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In general, MA occurs in the following order of frequency: intracavitary, peripheral, and intracranial arteries, respectively. 117 Previous studies reported the frequency of atherosclerotic aortic aneurysms and intracavitary MA but did not address MAs located elsewhere. In 22 000 autopsies performed at Boston City Hospital from 1902 through 1951, aortic aneurysms were detected in 1% to 5% of autopsies, but MAs were reported in only 1.5% of these.…”
Section: Frequencymentioning
confidence: 99%
See 4 more Smart Citations
“…In general, MA occurs in the following order of frequency: intracavitary, peripheral, and intracranial arteries, respectively. 117 Previous studies reported the frequency of atherosclerotic aortic aneurysms and intracavitary MA but did not address MAs located elsewhere. In 22 000 autopsies performed at Boston City Hospital from 1902 through 1951, aortic aneurysms were detected in 1% to 5% of autopsies, but MAs were reported in only 1.5% of these.…”
Section: Frequencymentioning
confidence: 99%
“…127 Among cases associated with IE or prosthetic valve endocarditis, 55% to 77% occur in the middle cerebral artery and 18% in the posterior cerebral artery; they occur less commonly in the anterior cerebral artery. 112,117,119 Multiple ICMAs occur in up to 25% of cases. 112,127,128 Pathogenesis ICMA most often occurs as a result of hematogenous spread or, less likely, as a result of contiguous spread.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
See 3 more Smart Citations